Hilbert‐Huang Transform Analysis of the Concentration Field of a Two‐Layer Impinging Stream Mixer. Issue 9 (8th August 2022) - Zhang, Jianwei; He, Ziyu; Sha, Xinli; Feng, Ying; Dong, Xin
Abstract: The concentration field of a two‐layer impinging stream mixer was measured by the plane laser‐induced fluorescence (PLIF) technology, and the energy distribution of the concentration field was studied by Hilbert‐Huang transform. The Hilbert spectrum and marginal spectrum under different operational conditions were analyzed in the mixer. It is indicated that the energy of the concentration field firstly increased and then decreased with larger nozzle diameter and nozzle spacing. The energy of the concentration field incremented with the rise of the jet Reynolds number. According to the energy characteristic value Pi, the flow field of the impinging stream mixer was divided into three regions. It could provide a quantitative basis for identification of the flow regimes of impinging steam. Abstract : The concentration field of a two‐layer impinging stream mixer was measured by plane laser‐induced fluorescence. The original concentration signal was decomposed into a series of intrinsic mode functions (IMFs) by empirical mode decomposition. The Hilbert spectrum and marginal spectrum under different experimental conditions were obtained by Hilbert transform of each order IMF component.